Comparative Analysis of Distance Learning Systems in the United Arab Emirates and the United States of America - Nalyvaiko, Oleksii; Khomenko, Albina; Vereshchak, Daria; Poliakov, Danilo (Educational Challenges, 2021)
The article is devoted to the current problem of distance learning. In the theoretical field, various aspects of the functioning of distance education are considered on the example of the analysis of the works of leading scientists in this field. The main aims of this research are: to analyze some of the best educational systems in the world (including distance learning) – systems of the USA and the UAE; to describe the main features of distance education in the USA and the UAE; to make some proposals, based on the experience of these countries, to optimize the system of distance education in Ukraine; to analyze the opportunities of their implementation and adaptation in Ukrainian education institutions. The theoretical basis of the study was open sources of information and educational portals of leading higher education institutions in the UAE and the United States. The methodology is the following. The theoretical framework of the study presents the leading experience of implementing distance learning of students in the context of state and educational policy of the represented countries. A comparative analysis of educational systems in the UAE and the United States is done within the framework of the introduction of distance learning. The study presents the research results, they are the proposals for optimizing the process of distance learning in Ukraine based on the experience of the UAE and the United States. The main ones are: development of criteria, requirements and recommendations for distance learning based on the following indicators: a) the amount of educational material; b) course duration; c) duration of the lesson d) technical requirements (e.g., the availability of a headset, a stable Internet connection, etc.); providing students and pedagogical staff with the necessary material and technical resources and checking the compliance of material and technical support with the educational requirements; establishment of centers for quality control of the distance learning process. The conclusions present the prospects of the study: developing of future comparative studies of distance learning systems; finding the most effective ways to make distance learning process better; elaborating and reasoning new approaches of teaching in the conditions of distance learning; setting up new platforms, applications, videos and so on in order to provide the process of distance learning; finding perspective directions of developing distance education and so on.